The Cord Blood Insulin and Mitochondrial DNA Content Related Methylome - Reimann, Brigitte; Janssen, Bram G.; Alfano, Rossella; Ghantous, Akram; Espín-Pérez, Almudena; de Kok, Theo M.; Saenen, Nelly D.; Cox, Bianca; Robinson, Oliver; Chadeau-Hyam, Marc; Penders, Joris; Herceg, Zdenko; et al. (Frontiers in Genetics, 2019)
Mitochondrial dysfunction seems to play a key role in the etiology of insulin resistance. Already at birth a link has been established between mitochondrial DNA (mtDNA) content and insulin levels in cord blood. In this study, we explore shared epigenetic mechanisms of the association between mtDNA content and insulin levels. We first assessed the association between cord blood insulin and mtDNA content in 882 newborns of the ENVIRONAGE birth cohort. Then, in 179 newborns cord blood DNA methylome and transcriptome were determined using the human 450K methylation Illumina and Agilent Whole Human Genome 8 × 60 K microarrays respectively. Cord blood mtDNA content was established via qPCR, while cord blood levels of insulin were determined using an electrochemiluminescence immunoassay. We performed an epigenome-wide association study (EWAS) adjusted for different maternal and neonatal variables and assigned the transcriptomic correlates to corresponding pathways employing the R packages ReactomePA and RDAVIDWebService. On the regional level we examined differential methylation using the DMRcate and Bumphunter packages in R. Cord blood mtDNA content and insulin were positively correlated (r = 0.066, p = 0.028) still showing a trend after additional adjustment for maternal and neonatal variables (r = 0.3, p = 0.061). We found an overlap of 33 pathways which were in common between the association with cord blood mtDNA content and insulin levels, including pathways of neuronal development, histone modification, CYP-metabolism and biological ageing. We further identified a DMR annotated to Repulsive Guidance Molecule BMP Co-Receptor A (RGMA) linked to cord blood insulin as well as mtDNA content. We described novel genes and pathways on multiple levels jointly related to both parameters. Metabolic variation in early life represented by neonatal insulin levels and mitochondrial DNA content might reflect or accomodate alterations in neuronal development, histone modification, CYP-metabolism and biological aging.